2013
DOI: 10.1186/1472-6882-13-152
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of geniposide on human neuroblastoma cells in the presence of formaldehyde

Abstract: BackgroundFormaldehyde can induce misfolding and aggregation of Tau protein and β amyloid protein, which are characteristic pathological features of Alzheimer’s disease (AD). An increase in endogenous formaldehyde concentration in the brain is closely related to dementia in aging people. Therefore, the discovery of effective drugs to counteract the adverse impact of formaldehyde on neuronal cells is beneficial for the development of appropriate treatments for age-associated cognitive decline.MethodsIn this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 30 publications
(48 reference statements)
0
18
0
Order By: Relevance
“…Overall the information above suggests that FA damages a number of tissues, reduces their antioxidant capacity [6,19,20,39,47,48,49], and impairs energy metabolism regulation [9]. Antioxidant molecules can help prevent or elimination this damage [6,19,20,39,47,48,49].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Overall the information above suggests that FA damages a number of tissues, reduces their antioxidant capacity [6,19,20,39,47,48,49], and impairs energy metabolism regulation [9]. Antioxidant molecules can help prevent or elimination this damage [6,19,20,39,47,48,49].…”
Section: Introductionmentioning
confidence: 97%
“…Many studies with FA have shown that it causes oxidative stress, also indicated by the fact that therapeutic antioxidant administration reduces the damage [6,39,48]. It is now essential to offset the harmful effects of FA, which is commonly used not only in medicine, but also in daily life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GP and PNS were obtained from the National Institutes for Food and Drug Control (China). TLJN was prepared by mixing extracts of gardenia and pseudoginseng in proportions determined using HPLC in previous experiments [23]. TLJN contains 10 parts GP to one part Rg1.…”
Section: Methodsmentioning
confidence: 99%
“…Conditions were as for Figure 6, except cellular morphology (A) and cell density (B) were GP+FA, TLJN+FA, PNS+FA, FA alone, and saline as indicated (provided by Sun et al [23]). Cells with no treatment were used as control.…”
Section: Figure S2mentioning
confidence: 99%